Produção de biomassa aérea, teor e rendimento de extrato das folhas de crajiru [Arrabidaea chica (Bonpl.) B. Verl.] em função de adubação orgânica em Manaus, AM - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
The Arrabidaea chica specie, also known as crajiru, pariri, chica, cross-vine, among other names, belongs to the Bignoniaceae family. It is commonly used to treat wounds, impigem, skin diseases of different origins, and ovarian inflammations, conjunctivitis, intestinal cramps, etc. This work aimed to evaluate the production of biomass, content and yield of crajiru extract for different sources of organic fertilizer in Manaus, AM. The seedlings were obtained from cuttings and planted in polystyrene trays (72 cells) with a commercial substrate, which remained in nursery for 60 days before being planted in field, with spacing of 1.0 m x 1.0 m. The experiment was conducted in a factorial arrangement 5x3 with a randomized block design where levels of factors were different sources of organic fertilizer: compost 5.0 kg/m2, chicken manure 3.0 kg/m2, guarana bark 4.0 kg/m2, cattle manure - 4.0 kg/m2 and control (absence), and the three crajiru morphotypes. After 240 days the production of leaves and stems, leaf / stem relation, nutritional analysis of leaves, content and yield of extracts were evaluated. The data were submitted to analysis of variance and averages the Tukey Test at 5% probability. It was observed that the sources of organic fertilizer promoted better development for the plants of A. chica, except for morphotype 1 which showed no significant differences in relation to the sources used, and the chicken manure was the fertilizer provided higher nutrient concentrations, biomass production, content and yield of extracts.
Keywords: Bignoniaceae; Adubos orgânicos; Plantas medicinais; Produção vegetal; Bignoniaceae; Organic fertilizers; Medicinal plants; Crop production; CIÊNCIAS AGRÁRIAS: AGRONOMIA